2020
DOI: 10.1186/s13054-020-2767-0
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-limiting treatment strategies among sepsis patients in the ICU: a retrospective causal analysis

Abstract: Objective: In septic patients, multiple retrospective studies show an association between large volumes of fluids administered in the first 24 h and mortality, suggesting a benefit to fluid restrictive strategies. However, these studies do not directly estimate the causal effects of fluid-restrictive strategies, nor do their analyses properly adjust for time-varying confounding by indication. In this study, we used causal inference techniques to estimate mortality outcomes that would result from imposing a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The accumulating evidence of harm associated with higher fluid volumes and positive fluid balances in sepsis in the ICU setting, 8,14,37‐40 and in a limited resource ED setting 41 raises several questions about the use of fluid for ED patients with less severe infection. Is IV fluid beneficial for those who can take oral fluids, only in those who cannot, or only in those with higher acute disease severity?…”
Section: Discussionmentioning
confidence: 99%
“…The accumulating evidence of harm associated with higher fluid volumes and positive fluid balances in sepsis in the ICU setting, 8,14,37‐40 and in a limited resource ED setting 41 raises several questions about the use of fluid for ED patients with less severe infection. Is IV fluid beneficial for those who can take oral fluids, only in those who cannot, or only in those with higher acute disease severity?…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of studies have reported that early large-volume uid therapy may increase mortality in patients [1,4,5,19]. Sadaka et al reported that mortality in patients with septic shock with uid volumes < 6 L at 24 h was signi cantly lower than that in patients with uid volumes of 6 L [11].…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines of the Surviving Sepsis Campaign recommend that uid resuscitation should be started early with a 30-ml/kg uid balance [2]. However, recent reports suggested that super uous uid may increase mortality in sepsis patients [3][4][5][6][7][8][9][10]. A few studies reported that appropriate restriction in 24-h uid therapy may reduce mortality [7][8][9][10], and excessive uid therapy can aggravate tissue and organ edema and increase the incidence of AKI (acute kidney injury) and other complications [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also reported on fluid management strategies for patients with sepsis. Causal inference technology is used to estimate the mortality outcome caused by the “caps” setting of fluid volume administration in the first 24 h in ICU ( 36 ). It was found that if the total amount of fluid in these patients is limited to 6–10 L, the 30-day mortality rate may be lower than the mortality rate observed in current practice.…”
Section: Application Of Ai In the Management Of Patients With Sepsismentioning
confidence: 99%